Hybrid Robust Optimization for the Design of a Smartphone Metal Frame Antenna - Sungwoo Lee; Jong Min Lee; Keum Cheol Hwang; Sanguk Park; Soonyong Lee (International Journal of Antennas and Propagation)
Hybrid robust optimization that combines a genetical swarm optimization (GSO) scheme with an orthogonal array (OA) is proposed to design an antenna robust to the tolerances arising during the fabrication process of the antenna in this paper. An inverted-F antenna with a metal frame serves as an example to explain the procedure of the proposed method. GSO is adapted to determine the design variables of the antenna, which operates on the GSM850 band (824–894 MHz). The robustness of the antenna is evaluated through a noise test using the OA. The robustness of the optimized antenna is improved by approximately 61.3% relative to that of a conventional antenna. Conventional and optimized antennas are fabricated and measured to validate the experimental results.